Efektivitas Penggunaan Media Saku Pintar Digital terhadap Kemampuan Klasifikasi Matematika Anak Usia 4–5 Tahun di Taman Kanak-kanak - Lathifah Afra Amani; Serli Marlina (STKIP Subang, 2025)
This study aims to examine the effectiveness of using Digital Smart Cards on the mathematical classification abilities of 4–5-year-old children at the UNP Padang Laboratory Development Kindergarten. The study used a quantitative approach with a quasi-experimental design of the non-equivalent control group type. The study population included all students at the UNP Padang Laboratory Kindergarten, while the sample was determined using purposive sampling, specifically classes A1 and A2, each consisting of 12 children. The research instrument consisted of a validated mathematical classification ability test developed by experts. Data analysis included a prerequisite test, independent sample t-test, and effect size calculation using the SPSS 26.0 for Windows. Data analysis was conducted through a prerequisite test, independent sample t-test, and effect size calculation using SPSS 26.0 for Windows software. The results showed that in the experimental group using digital smart pockets, the average pre-test score of 32.08 increased to 45.33 on the post-test. Meanwhile, the control group using conventional learning methods (number cards) showed an increase from 32.58 to 40.58. The t-test. The t-test yielded a significance value (2-tailed) of 0.000, indicating a significant difference between the two groups. The effect size value of d = 2.22 falls into the category of very strong effect (d > 1). Therefore, the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. It can be concluded that the use of digital smart pocket media is effective in improving the mathematical ability of young children at the UNP Padang Laboratory Development Kindergarten.